2020
DOI: 10.3892/etm.2020.8426
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA XIST promotes glioma proliferation and metastasis through miR‑133a/SOX4

Abstract: Glioma is the most common malignant brain tumour in adults, and the aetiology and mechanism of this tumour remain largely unknown. Previous studies have demonstrated that the long non-coding RNA X-inactive specific transcript (XIST) is upregulated in many cancers, and a high expression level of XIST is associated with poor clinical outcome. In the present study, the expression and function of XIST were investigated in the glioma cell line U251. XIST and microRNA (miR)-133a levels in glioma cell lines were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“… 24 The anti-proliferatory (decreased by 20.51 ± 2.43% and 19.76 ± 1.85%, 70.42 ± 6.91% and 66.39 ± 6.53%, as well as 69.42 ± 7.68% and 63.66 ± 6.59% at the 24th, 48th h, and 72nd h, respectively), anti-invasive (from 96.55 ± 8.57 to 35.38 ± 4.19 and from 129.26 ± 11.12 to 45.63 ± 4.15), anti-migratory (from 136.25 ± 15.42 to 41.74 ± 5.26 and from 158.97 ± 16.23 to 53.36 ± 7.48) and pro-apoptotic (from 8.14 ± 0.82% to 26.45 ± 2.65% and from 6.93 ± 0.71% to 23.91 ± 2.36%) properties of miR-133a have been underscored in further functional experiments in A549 and H1299 cells. More importantly, the anti-metastatic role of miR-133a in vivo has also been highlighted in glioma 25 and gastric cancer, 26 which were largely consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“… 24 The anti-proliferatory (decreased by 20.51 ± 2.43% and 19.76 ± 1.85%, 70.42 ± 6.91% and 66.39 ± 6.53%, as well as 69.42 ± 7.68% and 63.66 ± 6.59% at the 24th, 48th h, and 72nd h, respectively), anti-invasive (from 96.55 ± 8.57 to 35.38 ± 4.19 and from 129.26 ± 11.12 to 45.63 ± 4.15), anti-migratory (from 136.25 ± 15.42 to 41.74 ± 5.26 and from 158.97 ± 16.23 to 53.36 ± 7.48) and pro-apoptotic (from 8.14 ± 0.82% to 26.45 ± 2.65% and from 6.93 ± 0.71% to 23.91 ± 2.36%) properties of miR-133a have been underscored in further functional experiments in A549 and H1299 cells. More importantly, the anti-metastatic role of miR-133a in vivo has also been highlighted in glioma 25 and gastric cancer, 26 which were largely consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…And miR-133a can function as a regulator of cancer metastasis by targeting SOX4, MMP9, etc. 34 , 35 . This study focused on the regulatory effect of miR-133a on GEF-H1 /RhoA, and tended to add a new branch to its regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…They observed negative regulation between XIST and miR-133a in glioma cell lines. Their study reported that overexpression of miR-133a prevented glioma cell proliferation, metastasis and EMT by reducing the expression of SOX4 [ 159 ]. Consistently, other miRNAs, such as miR-429 [ 160 ], miR-210 [ 161 ], miR-92b [ 162 ] and miR-204-5p [ 163 ] may also modulates the expression of XIST in gliomas.…”
Section: Overview Of Long Non-coding Rnas In Glioblastomamentioning
confidence: 99%